Enhanced Charge Transport in Tantalum Nitride Nanotube Photoanodes for Solar Water Splitting. Issue 16 (17th July 2015) - Wang, Lei; Nguyen, Nhat Truong; Zhou, Xuemei; Hwang, Imgon; Killian, Manuela S.; Schmuki, Patrik
Abstract In the present work we grow anodic self‐organized Ta2O5 nanotube layers, which are converted by ammonolysis to Ta3N5 nanotubes, and then are used as photoanodes for photoanalytic water splitting. We introduce a two‐step anodization process that not only improves order (reduced growth defects) and overall light absorption in the nanotube layers, but also provides a significantly reduced interface charge resistance at the nitride/metal interface due to subnitride (TaNx) formation. As a result, such nanotube anodes afford a 15‐fold increase of the photocurrent compared with conventional nanotubular Ta3N5 electrodes under AM 1.5 G simulated sunlight (100 mW cm−2) conditions.